Therapeutic Effect of Topical Ointment Ethanol Extract From Patiwala Leaves (Lantana camara) on Histological Profile of Incision Wounds in Diabetic Rat Models - Theosobia Grace Orno; Anita Rosanty; Ratih Feraritra Danu Atmaja; Zulfikar Ali Hasan; Tuty Yuniarty; Ahmat Rediansya Putra (Biology, Medicine, & Natural Product Chemistry, 2025)
Diabetic wounds are one of the neurovascular complications of diabetes. Hyperglycemia complicates the healing of diabetic wounds, which are susceptible to infection and chronic inflammation. Topical treatment using herbal extracts aims to reduce the side effects of surrounding tissue damage. A topical ointment made from ethanol extract of Patiwala (Lantana camara) leaves, which has been tested for product quality, has antibacterial and anti-inflammatory effects that has been proven to help accelerate the healing of diabetic wounds in rats through parameters such as reduced wound diameter, changes in the number of fibroblast cells, and collagen fiber formation seen in the histological profile during 21 days of therapy with a concentration of 15% (p>0.05) compared to the positive control of 10% betadine.